The concept of Litigation in folklore and written literature - Yerzhan, Aryn; Tanzharikova Alua, Zhanalik Baltabayeva,; Maira, Zhunissova; Zeinep, Osmanova (Opción, 2020)
This article attempts to reveal the nature of the concept of litigation by conducting a conceptual analysis of language units in oral and written literature using cognitive data on the history of the population. As a result, the global character of the transformations, happening in the world, is caused, first, by the humanization of social life. The culturological approach becomes leading in comparative researches. In conclusion, Kazakh writers embodied the highest principles of morality, such as morality and justice, human dignity and reason, through the image of a fair judge